(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article identifies effective methods and tools that are important in the formation of innovative thinking skills of elementary school students, the use of integrative approaches and variable programs adapted to their complex development characteristics, innovative thinking in children based on a creative approach in the process of educational activities. the use of methods aimed at the formation of skills, didactic games and determining their place in the formation of children’s innovative thinking skills, the wide application of innovative technologies in educational processes, the innovative thinking of elementary school students A general analysis of theoretically based approaches to the problems aimed at improving the content, methods and forms of skills formation and methodology based on modern approaches is described.